An analysis of motives participation and sport achievement among under 17 years old football player in Jitra / Siti Norfarahim Azmil - Azmil, Siti Norfarahim (2018)
The study investigated an analysis of motives participation and sport achievement among under 17 years old football player in Jitra. In Malaysia, Malaysian's football team currently sill at 158th place out of 211 listed football team in the world stated by FIFA (2017) even though RMI.2 billion was spent for purpose of development of Malaysian football performance in Malaysian Budget 2017. Despite of this issues, there are lacked of research being done. This study tries to revealed is there any impact to the sport achievement according to their motives participation among under 17 years old football player in Jitra. 134 football player aged 13 years old until 17 years old were selected. A self-structured Participation Motives Questionnaire (PMQ) was administrated on the participants, to elicit their perceived impact of motives participation on their sport achievement. The factors of motives participation that includes in the questionnaire were: Physical condition, Heterosexuality, Team, Fun, Ability, Winning, Health, Relaxation and Social approval were examined. Descriptive statistical (mean, standard deviation, one-way ANOVA) were used in this research. It was discovered that under 17 years old football player in Jitra has impact on their sport achievement according to motives participation. In conclusion, the study suggested ways to help improve the motives participation of football player which is under 1 7 years in Jitra, since motives participation is the foundation for their sport achievement.